Some thoughts on the morphotectonic development of the Denizli region Basic - Yücel Yılmaz (Bulletin of the Mineral Research and Exploration, 2022)
The Denizli region is located to the east of the Buldan Horst. Although they follow the same trends as the Büyük Menderes and Gediz Grabens, the Denizli region has undergone semi-independent evolution during the Quaternary. The essential morphotectonic elements of the area are the Denizli Basin and the surrounding Babadağ and the Güzelpınar Horsts. The Babadağ Horst is the most distinct morphotectonic element of the region. It is bounded in the north by the Denizli fault, a listric normal fault, and possibly a major detachment fault. The Laodicea and Güzelpınar Horsts located within the downthrown block of the fault may be regarded as antithetic structures.